2021
DOI: 10.1186/s12871-021-01386-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing leakage during continuous femoral nerve catheter fixation using 2-octyl cyanoacrylate glue (Dermabond®): a randomized controlled trial

Abstract: Background Continuous peripheral nerve catheters (CPNCs) have been used for postoperative pain relief. A common problem encountered with CPNCs is pericatheter leakage, which can lead to dressing adhesive failure. Frequent dressing changes increase the risk of catheter dislodgement and infections. Adhesive glue is effective in securing the peripheral nerve catheter and decreasing leakage around the catheter insertion site. This study aimed to evaluate the incidence of pericatheter leakage with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…One of the problems in performing CPNB is the leakage of local anesthetic from the catheter insertion site. The use of glue at the puncture site [ 8 , 16 ] and tunneling of catheters [ 17 ] have been reported to be effective in preventing leakage; however, both of these methods require extra costs and invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems in performing CPNB is the leakage of local anesthetic from the catheter insertion site. The use of glue at the puncture site [ 8 , 16 ] and tunneling of catheters [ 17 ] have been reported to be effective in preventing leakage; however, both of these methods require extra costs and invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic approaches, where materials are developed with molecularly designed macromolecular backbones, enable control over the physical and chemical properties of the hydrogel such as swelling, charge, etc. Synthetic hydrogel-based internal hemostatic sealants for cardiac reconstruction and pulmonary repair have been commercialized and developed based on PEG (e.g., CoSeal, Progel, and Tridyne) and cyanoacrylates (Dermabond) as well as natural components such as gelatin (Floseal), BSA (BioGlue), and fibrinogen (Tisseel and Evicel) . Recently, Quan et al reported strategies to design hemostatic biomaterials through cross-linking 2,3-diaminopropionic acid (DapA) with a graphene oxide (GO) sponge, as shown in Figure .…”
Section: Hemostatic Materials and Reagentsmentioning
confidence: 99%